78.2k views
1 vote
Evaluate the expression for p = 4, q = 2, and r = 1.
(−p)^2q^-2

1 Answer

5 votes

Final answer:

To evaluate the expression (-p)^2q^-2 for p = 4, q = 2, and r = 1, substitute the given values into the expression. The final value is 4.

Step-by-step explanation:

To evaluate the expression (−p)^2q^-2 for p = 4, q = 2, and r = 1, we substitute the given values into the expression.

First, let's calculate (-p)^2:

(-p)² = (-4)²= 16

Next, let's calculate q^-2:

q⁻² = (2)⁻² = 1/2²= 1/4

Now, substitute the calculated values back into the expression:

(−p)²q⁻²= 16 * (1/4) = 4

User Mozcelikors
by
4.9k points